Self-Medication Practices Among the General Public During COVID-19 Pandemic Era-A Cross- Sectional Study. - Sindhura Nagisetty; T. Tulasi Madhuri; J. Naga Sreenivasulu; K.P. Poojitha; B. Ramesh; P. Jagadeesh (International Journal of Pharma and Bio Sciences, 2023)
The practice of self-medication in the general public reached to highest level during the COVID-19 pandemic. Hospital admissions are less during the third wave. Most of the COVID-19 patients took treatment from home during 3rd wave. This study aims to evaluate the self-medication methods and practices in the general public and its impact on society. This retrospective observational cross-sectional study and the sample size were taken as 350 based on a previous study. The general public was approached via digital and social platforms and was given a pretested and validated questionnaire. The questionnaire was designed and sent as Google Forms. The questions are being given regarding self-medication practices. The education status of about 91% of the participants is graduation and higher. Sources of information for 67% of participants were doctors, 13% were family and friends, and 9% were pharmacies. 44% of them took self-medication for the prevention of COVID-19, and the majority of these people preferred homeopathy medication. About 54.4% of people took self-medication in the past 6 months for cold, cough, and sore throat. About 55% of them took antihistamines and vitamins D and C to relieve symptoms. In addition, 22% of the participants took antibiotics like Azithromycin-500mg once daily and Amoxicillin and Clavulanic acid twice a day 650 mg for 5 days to relieve the symptoms. The availability of drugs at home was one of the significant reasons for following self-medication practice, according to 52% of them. 44% of them reported 100% improvement in their symptoms. However, about 15% of them experienced mild adverse effects, like diarrhea, nausea, and stomach pain, with their self-medications. Self-medication without proper guidance and knowledge regarding the medicines is not advisable. Irrational use of drugs, especially antibiotics, can lead to the development of antimicrobial resistance.